2021
DOI: 10.1007/s10047-021-01298-w
|View full text |Cite
|
Sign up to set email alerts
|

Multiple organ retrieval in a brain dead left ventricular assist device donor

Abstract: Left ventricular assist device (LVAD) support in donors may contribute in preserving proper haemodynamics and systemic perfusion during organ retrieval thus decreasing the risk of multiple organ injury. This is an option to expand the current organ supply. We report on intra-abdominal organs procurement strategy in a selected LVAD recipient who suffered a fatal cerebrovascular accident at the time of COVID-19 pandemic outbreak. The liver and kidneys grafts have been successfully transplanted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The main manifestations of heart disease in CKD include left ventricular hypertrophy, acute and chronic heart failure, and coronary artery disease. However, LVF is the most serious pathological change and is an important risk factor for a series of cardiovascular and cerebrovascular events [ 4 , 12 ]. Multiple studies have shown that LVF is an important predictor of CVD death in dialysis patients [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main manifestations of heart disease in CKD include left ventricular hypertrophy, acute and chronic heart failure, and coronary artery disease. However, LVF is the most serious pathological change and is an important risk factor for a series of cardiovascular and cerebrovascular events [ 4 , 12 ]. Multiple studies have shown that LVF is an important predictor of CVD death in dialysis patients [ 13 ].…”
Section: Discussionmentioning
confidence: 99%